ALEXA, IS AMAZON A SURVEILLANCE CAPITALIST? PRIVACY ISSUES AND OTHER CONCERNS REGARDING THE SURVEILLANCE CAPITALIST ECONOMIC LOGIC - Paniagua Delgado, Jenniffer (Université d'Ottawa | University of Ottawa, 2020)
As cyberspace has become an important part of our everyday life, we can come across with plenty of smart devices, sometimes even without realizing it. Data collection has become a normality, but a big part of that data goes for undisclosed commercial practices of extraction, prediction, and sales. Therefore, it is important to understand the reasons behind that data collection and whether our confidential information is being protected or actually used against us. Zuboff explains the surveillance capitalist economic logic conveying the theoretical framework she created with real-world experiences and cases. It is clear here, that surveillance capitalism presents a current threat to cyberspace and the way we interact with it. Moreover, Zuboff acknowledges through her book the existence of evidence that suggests Amazon is directed towards surveillance capitalist methods. This study aimed to prove that this, in fact, is the case. This information was obtained paying close attention to interviews, press releases, company programs, and policies related to Amazon. Through this paper, it has become evident that Amazon has, and plans to continue having, surveillance capitalist practices. It is important to scrutinize Amazon and other big tech companies that claim to protect its users. The reality is different since, at the end of the day, companies serve their own interests. Keywords: Amazon, behavioral modification, cyberspace, privacy, surveillance capitalism.